PENGARUH EKONOMI MAKRO TERHADAP JAKARTA ISLAMIC INDEKS 70 TAHUN 2019-2023 - Tsaury Manalu, Sofyan; Hasan, Asyari; Lutfi, Mohammad (ITB AAS Indonesia Surakarta, 2025)
This research aims to analyze the influence of macroeconomic factors on the Jakarta Islamic Index 70 (JII 70), with a focus on inflation, BI 7 Day Repo Rate (BI 7 DRR), and economic growth (GDP). The method used is quantitative research with a time series approach using secondary data obtained from the Central Statistics Agency (BPS), Bank Indonesia, OJK, and IDX for the 2019–2023 period. The data analysis technique uses Eviews software to test the relationship between macroeconomic variables and the movement of the JII 70. The results of the research show that inflation has a significant negative influence on the JII 70, which means that an increase in inflation tends to reduce the movement of the stock index. BI 7 DRR, on the other hand, has a positive effect on JII 70 movements, where an increase in the benchmark interest rate tends to increase share prices. Apart from that, economic growth as measured by GDP also has a positive effect on JII 70, reflecting that the increase in GDP is in line with the increase in share prices. These findings provide important insights for investors and policy makers in understanding the dynamics of the Indonesian stock market, especially in the context of the Islamic financial sector.